A Systematic Mapping of IoT Sensor Networks for VANETs supported by Edge Computing for Road Blind Spots - Menezes, Sandro Andrade Monteiro; Trindade, Eric Lisboa; Matos Junior, Rubens de Souza; Machado, Antonio Aliberte de Andrade; Nascimento, Bruno Santos; Porfirio, Iara Angelino; Cruz, Cleide Ane Barbosa da; Santos, Marcos Pereira dos (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2023.236473, 2023)
As part of a technological evolution, the Internet of Things - (IoT) has been showing changes both in terms of hardware and software. In particular, IoT protocols have brought some differentiated changes by acting particularly on devices with low processing power, low energy consumption and little RAM, these restrictions must be carefully evaluated to guarantee aspects of performance and functionality within the characteristics of this environment. In this way, the present work presents a systematic mapping of literature about the use of sensors to support an anticollision system in VANET (Vehicular Ad-hoc Networks), V2V (vehicle to Vehicle) and V2I (Vehicle to Infrastructure) networks. Through this mapping we also evaluate the use of Edge computing architecture, in order to produce lower latency and consequently a more adequate response time to the needs of the scenario.